The new Japanese Firm as a Hybrid Organization - Miyamoto, Mitsuharu (Evolutionary Economics and Social Complexity Science,, 2018)
This book examines corporate reform in Japan by focusing on corporate governance and the employment system. Contrary to a prevailing assertion of radical change, it is revealed that actual change is gradual, and a new type of Japanese firm is generated by reform with gradual change. Throughout the book, Japanese firms are seen to be evolving through gradual institutional change. Chapter 1 discusses how Japanese corporate governance changed incrementally and cumulatively to rebuild management and restore corporate performance. Chapter 2 focuses on reform in work organization and discusses how performance-related pay was introduced in tandem with corporate governance reform. It is shown that the practice of long-term employment has been maintained despite the prolonged depression and mounting pressure to shift to shareholder-oriented corporate governance. Chapter 3 investigates how Japanese firms are diversified into four types, based on whether performance-related pay is introduced and whether long-term employment is maintained. The author demonstrates that major Japanese firms reconstruct their organization as hybrid structures based on a combination of long-term employment and performance-related pay. Chapter 4 investigates how performance-related pay actually operates. It is analyzed by distinguishing the three main objectives to be attained by performance pay: succeeding in individual performance, contributing to overall organization performance, and meeting the challenge of new tasks. Finally, Chapter 5 investigates how employees react to changes in corporate governance. Using survey data, the book shows that Japanese employees approve of increasing shareholder value, regarding it as corporate value. They not only approve the monitoring of management by shareholders, but also demand a part in the monitoring. Employees seek to be engaged in corporate governance-a true challenge for a Japanese corporation.